Pendampingan UMKM Batik CV. Wecono Asri dalam Meningkatkan Jumlah Peminat Melalui Pameran di Car Free Day Jl. Dhoho Kota Kediri - Yunitasari, Dinna; Rosyidah, Lu'lu' Nur; Rohmah, Lailatul; Ningsih, Dila Fitria Cahya; Afiyana, Rizka Lailatul; Febrianti, Nabilla Ayu (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2023)
Batik is a cultural heritage that is still preserved today. UNESCO has even named it in the category of cultural heritage. Batik, which was only used by the royal family, became the clothing commonly used by the people. But now, many people are starting to leave batik. Especially young people who think batik is too outdated. By holding the exhibition, it's intended to introduce batik from CV. Wecono Asri to the wider community. The method used in this study is the PAR method. The implementation of the method is divided into three stages. The first stage is planning, observation, and implementation. There are two strategies for implementing the exhibition, namely offering products in front of the exhibition stand and going around to introduce the product to visitors. The results obtained from the exhibition held at Car Free Day (CFD) Dhoho Street, City of Kediri, are that more and more people know batik from CV. Wecono. proved by the presence of several visitors who were interested in looking around and asking questions about the batik products produced by CV. Wecono Asri. In the future, batik producers could use colors and designs that could attract the interest of all groups, especially young people.